Pengelolaan Sampah Berbasis 3R (Reduce, Reuse, Recycle) dalam Meningkatkan Kualitas Lingkungan - Sunita Dasman; Elan Nurhadi; Listian Indriyati Achmad; Widiastuti; Nasrun Baldah; Reyhan Pajero (DPPM Universitas Pelita Bangsa, 2026)
Household waste management has become one of the major environmental challenges requiring active community participation. Limited public awareness and knowledge regarding proper waste management contribute to increasing environmental pollution and declining public health quality. This community service program aimed to enhance the knowledge, skills, and awareness of community members in managing household waste through the implementation of the 3R (Reduce, Reuse, Recycle) principles. The program was implemented through socialization, educational counseling, training, hands-on waste sorting practices, mentoring, and evaluation using pre-tests and post-tests involving 30 participants. The results demonstrated a significant improvement in participants' understanding of 3R-based waste management. The average score increased from 62.5 in the pre-test to 85.7 in the post-test, representing an improvement of 23.2 points (37.1%). In addition, participants began implementing the separation of organic and inorganic waste, recycling waste into economically valuable products, and establishing a community waste management group to ensure the sustainability of the program. The findings indicate that an educational approach combining theoretical instruction, practical activities, and continuous mentoring is effective in enhancing community capacity for sustainable waste management. Furthermore, the program contributed not only to improving environmental quality by reducing the volume of waste disposed of in landfills but also to creating economic opportunities through recycling activities. Therefore, the implementation of 3R-based waste management can serve as an effective community empowerment model for promoting a cleaner, healthier, and more sustainable environment.